Między ideologią a edukacją — refrakcje w herstorycznych biografiach dla dzieci - Matuszko, Kinga (Zagadnienia Rodzajów Literackich, 2024)
The aim of the article is to analyze refraction in selected herstory publications for children, presenting the biographies of famous female figures. The subject of reflection is: Stories for Kids Who Dare to Be Different: True Tales of Amazing People Who Stood Up and Stood Out by Ben Brooks, Good Night Stories for Rebel Girls: 100 Tales of Extraordinary Women vol. I and vol. II by Elena Favilli and Francesca Cavallo, Fantastically Great Women Who Changed the World and Fantastically Great Women Who Made History by Kate Pankhurst. The aim of this type of literature is to introduce unknown or less known historical female figures and to create new role models for children. However, the article points out that the authors of the discussed publications not only create too one-sided, simplified images of the heroines, ignoring their difficulties, mistakes and related controversies, but also often neglect other, private aspects of their lives in favor of talking about their careers and striving for power and wealth. In addition, in the books discussed there is an underutilization or only partial use of the potential hidden in the complicated and sometimes only partially recognized biographies of women. The writers selectively treat the biographies of ambiguous or controversial characters.